Influence of stress towards employee’s performance in oil and gas industry at Kuala Lumpur - Nur Annissa, Najib (2015)
This research is about the impact of stress towards employee‟s performance in oil and gas industry at Kuala Lumpur. The purpose of this research is to recognize whether the stress can influence employee‟s performance. This research is also to find how the sources of stress (conflict factor, role factor and workload factor) influence the overall impact of stress. 70 selected employees which were random representative including administrative, executive, supervisor or manager and others staff from oil and gas industries that answer the questionnaire given through email. The final result will describe the impact of stress towards employee‟s performance and actions required to reduce stress in oil and gas industry at Kuala Lumpur. In this research, the researcher will present the result of the research to prove the relationship between stresses towards employee‟s performance.